New bifunctional carbohydrate-like thiourea derivatives – design and first application in organocatalysis. Issue 15 (3rd August 2018) - Adam, Lutz; Schefzig, Luise; Pecchioli, Tommaso; Zimmer, Reinhold; Reissig, Hans-Ulrich
Abstract: From easily available aminopyran and aminooxepane derivatives and 2, 5-bis(trifluoromethyl)phenyl isothiocyanate the corresponding thiourea derivatives were prepared. One compound was further modified by introducing a tertiary amino group. The four catalysts were then examined as catalysts in a Michael addition of acetylacetone to β-nitrostyrene. A 1:1 mixture of one of these thioureas with an ( S )-prolinol derivative was also tested as catalyst, but no synergetic effect was found. The best yield achieved was 88% and the highest ee amounted to 39%. In a preliminary experiment, the aldol reaction of acetone with isatin was investigated. One catalyst provided the expected aldol product in low yield, but in excellent enantioselectivity. Graphical Abstract: